GENETIC AND INFECTIOUS MARKERS OF INFERTILITY - E. A. Levkova (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The report presents the results of own research of the most important factors in the genesis of various forms of sterility. A  married couples (n = 50) was examined with regard to possible  etiological structure of these forms of pathology — infections of the  family herpes (Herpes simplex types 1, 2, Cytomegalovirus hominis  (CMV), Epstein–Barr virus (EBV) and genetic distribution for the  second class of histocompatibilit (HLA II class): HLA-DRB1, HLA- DQA1 и HLA-DQB1. The authors present own data on genetic typing  of the couples for the second class of histocompatibility, which allow  to correlate these data with clinical and laboratory associations with  infectious agents (infections of the herpes family). The genetic  characteristics that determine the reproductive ability of the couple  are associated with susceptibility to certain infectious markers. It is  shown that the dominant majority of couples determined the HLA- DRB1 gene, which is more frequently associated with infections of  the herpes family. Despite the fact that the level of positive PCR results in the group of couples with primary infertility was  higher than in couples with secondary sterility (100 and 92%, respectively), maximum titers of specific antibodies to  infections of the herpes family, including the frequency of markers of exacerbation, definition of IgM was higher than in the group of  couples with primary infertility, and significantly higher than in  couples with normal fertility. So, this antigen histocompatibility  (HLA-DRB1) is associated with significant frequency of sterility,  especially the secondary one, and infectious contamination infections  of the family of herpes — HSV 1, 2 types, CMV, EBV in the study group — couples with secondary infertility. Marker HLA-DRB1,  the most frequent in coup les with infertility, including idiopathic,  associated in this group not only with significant contamination of  infectious of the herpes family, but the presence of a chronic  infectious process at the stage of reactivation. Conducted clinical and  immunological studies clearly demonstrate the need for  a comprehensive survey of women with disabilities in the system of  immunogenesis with the mandatory assessment of the level of  infectious (viral) contamination. Analysis of the results of their  clinical and immunological studies allows us to propose an algorithm  of complex examination in functional disorders in the system of  immunogenesis, including the study of viral load as a necessary  component.